A Qualitative Approach to Self-Employment and Social Protection: The Greek Case Within a Transforming World of Work and an Emerging Policy Paradigm - Varvara (Berry) Lalioti (Societies, 2025)
Following the 2008–2009 economic crisis, the issue of self-employed individuals’ access to social protection has gained increasing prominence at both supranational and national levels, often in relation to the rise of ‘bogus’ or economically dependent self-employment and its broader implications. More recently, the COVID-19 pandemic further exposed persistent gaps in the social protection of the self-employed, contributing to their comparatively more precarious position vis-à-vis wage earners. Against this backdrop, and drawing on a literature review alongside findings from a series of semi-structured interviews, this article uses Greece—a country where self-employment constitutes a structural feature of a highly fragmented labour market, and which records the highest self-employment rate in the EU-27 (and among the highest in the OECD)—as a case study to examine self-employment and access to social protection. This article contributes to the growing literature on the social protection of non-standard workers in a context marked by ongoing transformations in employment relations and the world of work. It illustrates, inter alia, the relative weakness of trade union representation for the self-employed, and how limited trust in state institutions among this group shapes their perceptions of social protection, thereby undermining the system’s sustainability.